Learning Strategies and Muhammadiyah Education at SMP Muhammadiyah 6 Krian the Covid-19 Pandemic - Nurma Alawiyah; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
The purpose of this study is to find out the state of education during the pandemic, more specifically to find out the learning strategies used to deliver material to students in the midst of the Covid-19 pandemic. In addition to the educational strategy, because schools are the objects under the umbrella of Muhammadiyah, Muhammadiyah education and the way it is delivered will be the objectives of this research article. This study uses a descriptive qualitative research method which is a research process to understand social or human problems by analyzing words to create a complex and comprehensive picture, to report views of detailed information obtained from information sources in the natural environment. The research found that SMP Muhammdiyah 6 Krian uses a personalized method in the discussion system. Here, the teacher provokes discussion and tests students' understanding through calling names one by one. In online learning, discussion sessions must be done to determine how much students understand the material provided. In addition to the personalized method, the teacher also uses a consultation method when offline learning takes place. The Covid-19 pandemic indirectly directs educators to think more creatively so that students can still receive and understand the material given well. Educators can combine offline and online learning methods by providing a variety of tasks to increase student understanding.